Economic valuation of the National Park of Brasilia - Angelo, Humberto; Almeida, Alexandre Nascimento de; Vasconcelos, Pedro Guilherme de Andrade; Gaspar, Ricardo de Oliveira; Paula, Maristela Franchetti de; Matricardi, Eraldo Aparecido Trondoli (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
This study aimed to analyze the willingness of the population to pay for the maintenance and conservation of the National Park of Brasília - NPB, valuing its environmental attributes and contributing to the improvement and preservation of the Conservation Unit. To this end, 385 questionnaires were applied during February, March and April of 2014. The profile of respondents’ willingness to pay was analyzed with a logistic regression. The estimated willingness to pay was R$ 9.31/month, paid mainly by people who know the NPB and with better economic situation. This shows that the population of interest revealed a significant desire to contribute to the park.